2020
DOI: 10.15295/bmij.v8i2.1475
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Volatility Spillover Effect Between Stock Markets of Turkey, Italy, Greece and Russia

Abstract: In this study, the volatility spillover effects in stock markets of various countries are examined. Volatility spillover effect occurs in two forms as heat wave and meteor shower in literature. From this point to these two effects were investigated in stock markets of Turkey, Italy, Russia and Greece. In the research, cointegration, ARCH-LM, VAR, and finally VAR-MGARCH analyzes were used. According to the results of the analysis, it was concluded that the volatility spillover effect is effective in all stock m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…These results indicated that Turkiye is tightly integrated into the global markets. Berberoğlu (2020) examined the volatility and spillover effects between the stock markets of Turkiye, Italy, Russia, and Greece from January 1 st , 2010 to December 31 st , 2018, by using cointegration, ARCH-LM, VAR, and VAR-MGARCH models. The results of the study showed that the volatility spillover effect is effective in all stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results indicated that Turkiye is tightly integrated into the global markets. Berberoğlu (2020) examined the volatility and spillover effects between the stock markets of Turkiye, Italy, Russia, and Greece from January 1 st , 2010 to December 31 st , 2018, by using cointegration, ARCH-LM, VAR, and VAR-MGARCH models. The results of the study showed that the volatility spillover effect is effective in all stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Standard and Poors (S&P500) borsa getirilerinin gelişmekte olan ülkeler Türkiye örneğini inceleyenBerument ve İnce (2005:64), vektör otoregresyon (VAR) modelini ve günlük verileri kullandıkları çalışmada Standart and Poors getirilerinin Borsa İstanbul'u dört güne kadar pozitif etkilediği sonucuna ulaşmışlardır. Türkiye, Yunanistan, İtalya ve Rusya borsalarındaki volatilite yayılımını inceleyenBerberoğlu (2020), Türk pay senedi borsasının diğer üç ülke borsasından etkilendiğini ancak volatilite yayılımının özellikle Rusya ve İtalya arasında olduğunu vurgulamıştır.Özellikle son dönemde Covid-19 pandemisi ve finansal krizlerin etkileri açısından incelendiğinde, Economist dergisi salgının küresel piyasalar için ciddi bir tehdit olduğunu belirtmiştir (The Economist 2020a). Örneğin Dow Jones Endüstri endeksi 9 ve 12 Mart 2020 tarihlerinde %12,93 ve %9,99'luk düşüşler kaydederken benzer şekilde Londra Borsa (FTSE 100) endeksi %24,8'lik bir düşüş yaşamıştır.…”
unclassified